Two New Species of Lauraceae from Espírito Santo, Brazil - Rodrigues De Moraes, Pedro Luís [UNESP]; Fernandes, Tamiris Bianca [UNESP]; Freitas Azevedo, Igor Henrique [UNESP]; Mouzinho Barbosa, Tiago Domingos [UNESP] (Harvard University Botany Libraries, 2019)
Two new species from the Brazilian Atlantic rainforest of Espírito Santo State, Licaria spiritusanctensis and Ocotea teresae, are described and illustrated. Their putative relationships within the respective genera are discussed. We also provide illustrations and comments on micromorphological and anatomical features of leaves of these new species, comparing them to those of congenerics and showing that they can be useful for recognition of different taxa.
Keywords: leaf cuticle; leaf vascular bundle; Licaria; Ocotea; taxonomy